A comparative dermoscopic and reflectance confocal microscopy study of naevi and melanoma with negative pigment network. (19th August 2019) - Farnetani, F.; Scope, A.; Mazzoni, L.; Mandel, V.D.; Manfredini, M.; Magi, S.; Vaschieri, C.; Kaleci, S.; Longo, C.; Ciardo, S.; Stanganelli, I.; Pellacani, G.
Abstract: Background: Negative pigment network (NPN) is a dermoscopic structure observed more frequently among melanomas than naevi. Precise tissue correlates of NPN are still elusive. Objective: To describe the reflectance confocal microscopy (RCM) findings underlying NPN in melanocytic neoplasms. Methods: We retrospectively identified all melanocytic neoplasms displaying dermoscopic NPN that were imaged with RCM and subsequently biopsied between 2011 and 2015. Images from study lesions ( n  = 50) were evaluated for dermoscopic and RCM Criteria. Histopathological correlational study was performed in a subset of cases ( n  = 15). Results: The study data set consisted of 21 melanomas (42%) and 29 naevi (58%). Melanomas showed more frequently irregularly shaped globules than naevi (62% vs. 28%, P  = 0.03); NPN also tended to be more asymmetrically located among melanomas (86%) than naevi (62%), albeit not significant ( P  = 0.06). Under RCM, we observed three patterns of dermal papillae (DP): (i) 'Dark DP' – whereby DP were devoid of nests and often surrounded by a junctional proliferation as thick‐Rings – this pattern was less common among melanomas ( n  = 10, 48%) than naevi ( n  = 23, 79%, P  = 0.02); (ii) 'Bulging DP' – whereby junctional nests of melanocytes protrude into the DP, often in association with junctional proliferation as Meshwork – with comparable frequency among melanomas ( n  = 12, 57%) and naevi ( n  = 23, 79%, P  = 0.09) and (iii) 'Expanded DP' – whereby junctional and/or dermal nests filled and expanded the DP, often in association with dermal–epidermal junction (DEJ) Clod pattern – seen more commonly among melanomas ( n  = 15, 71%) than naevi ( n  = 6, 21%, P  < 0.001). Dermoscopy–RCM correlation and comparison to histopathological findings show that the hypo‐pigmented lines of NPN correlate with broadened epidermal retes, which often show overlying surface dells and wedge‐shaped hypergranulosis, while the pigmented globules of NPN correlate with a predominantly‐junctiona of melanocytes along and between the elongated retes. Conclusions: Dermoscopic NPN correlates with three DEJ RCM patterns with differing frequency between naevi and melanomas.